Corrective Intra-Articular Osteotomy Using a 3D-Printed Model and Induced Membrane Technique for AO/OTA C3 Distal Femur Fracture with Articular Malunion and Metaphyseal Nonunion - Natsumi Saka; Yoshinobu Watanabe; Gen Sasaki; Hirotaka Kawano (Case Reports in Orthopedics)
Comminuted distal femur fracture is a challenging injury, and care must be taken to reduce the articular fragment and acquire the sufficient stability for the metaphyseal comminution. We report the case of a AO/OTA C3-type distal femur fracture with articular malunion and metaphyseal nonunion. Articular malunion was treated with corrective osteotomy using a 3D-printed model for planning, and metaphyseal nonunion was treated with an induced membrane technique. Conclusion. Two major complications in the comminuted periarticular fracture can be addressed by an osteotomy and induced membrane technique. A 3D-printed model is a useful tool to evaluate the morphology of the malunited articular surface.